2016
DOI: 10.1515/secm-2014-0094
|View full text |Cite
|
Sign up to set email alerts
|

Use of polyvinyl chloride (PVC) powder and granules as aggregate replacement in concrete mixtures

Abstract: Concrete is one of the materials in which polymer wastes are utilized. Generally, these wastes are added at specific rates in scientific studies but an important problem of waste polymers is size irregularity. Even when consistent dosage rates are used, variations in polymer size can lead to variability in the physical and mechanical properties of the concrete produced. The aim of this study is to determine physical and mechanical properties of polyvinyl chloride (PVC)-containing concretes. In order to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…Regardless of the filler-binder ratio, the water absorption of the composites reduced with an increase in binder content. The dry and wet flexural strength of the composites improved with an improvement in the filler-binder ratio, reaching the maximum value at a binder content of 30% (Choi et al 2006 ). However, bricks made from waste plastics like polyethylene, high-density compound (nylon 66) and polythene terephthalate along with red soil, river sand and stone crush in numerous compositions showed 0% water absorption value for plastic bricks and maximum compressive strength of 15.50kN when river sand was used with plastic waste.…”
Section: Utilization Of Plastic Waste In Construction Bricks Tiles and Blocksmentioning
confidence: 99%
“…Regardless of the filler-binder ratio, the water absorption of the composites reduced with an increase in binder content. The dry and wet flexural strength of the composites improved with an improvement in the filler-binder ratio, reaching the maximum value at a binder content of 30% (Choi et al 2006 ). However, bricks made from waste plastics like polyethylene, high-density compound (nylon 66) and polythene terephthalate along with red soil, river sand and stone crush in numerous compositions showed 0% water absorption value for plastic bricks and maximum compressive strength of 15.50kN when river sand was used with plastic waste.…”
Section: Utilization Of Plastic Waste In Construction Bricks Tiles and Blocksmentioning
confidence: 99%
“…According to Saikia and Brito [12] PET-aggregate incorporated concrete specimen had significantly lower resultant compressive strengths and the tensile strength to compressive strength ratio observed for all specimen having PET-aggregate were higher compared to conventional concrete, therefore the incorporation of PET-aggregate increases toughness behavior. According to Bolat and Erkus [15] the tendency of decreasing compressive strength by increase of polyvinyl chloride (PVC) ratio as aggregate replacement was attributed to decrease in adhesive strength between PVC surface and cement paste and the hydrophobic nature of PVC, that may resist water necessary for cement hydration from entering the concrete specimen structure during curing. According to Gopi et al [16], compressive strength decreased with increase in percentage of PET as fine aggregate partial replacement was attributed to increase in porosity of concrete and concrete proper bonding not taking place and the PET incorporated concrete indicated better performance for compressive strength up to 10 % of fine aggregate replacement, compared to those partially replaced with polypropylene (PP), attributed to the PET size being near sand gradation.…”
Section: Plastic/ Plastic Waste Properties Applicability and Effectmentioning
confidence: 99%
“…Fine aggregate take as 0-4 mm aggregates. The specific gravity of crushed limestone sizes 4.75 mm to 0.075 mm were 2.830 g/cm 3 according to Morova and Terzi [23], this value was used to convert volumetric to weight aggregate replacement for up to 4 mm aggregate replacement as indicated by Bolat and Erkus [15], assuming the fine aggregate is the up to 4 mm aggregates and any base value, materials, methods and other factors used for both studies were similar; * § % plastic weight replacement as indicated in source/calculated/converted Table I indicates the compressive strengths used for this study from reviews ranged between 66.8 MPa (adopted from Al-Hadithi, and Alani [19]) and 14.02 MPa (adopted from Gopi et al [16]) for the concrete having partial replacement of fine aggregate with plastic and the percentage of plastic replacement or addition were between 0.86% (adopted/modified from Shubbar and Al-Shadeedi [18]) to 45.19% (adopted/modified from Bolat and Erkus [15]) by weight of fine aggregate. Hasanzade-Inallu et al [24] used ANNs using MATLAB R2019a, to have different input and output variable to ranges that were similar; each variable was normalized by subtraction of its minimum, then divided by its range and the output must be denormalized by the reverse process.…”
Section: Review and Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, in the literature, it is possible to find numerous examples of the substitution of cement or aggregate with waste products [7][8][9][10][11][12], and plastic waste has been extensively studied in this scope [4,[13][14][15][16][17][18][19][20][21][22][23]. While mineral substitutions only slightly affect the mechanical properties of mortar or concrete, in the case of plastics, the experimental data all point in the direction of a significant loss in mechanical properties when such substitution occurs.…”
Section: Introductionmentioning
confidence: 99%